2001
DOI: 10.1103/physrevlett.87.147401
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Terahertz Surface Modes in Nanometer-Sized Liquid Water Pools

Abstract: The far-infrared absorption spectrum of nanometer-sized water pools at the core of AOT micelles exhibits a pronounced resonance which is absent in bulk water. The amplitude and spectral position of this resonance are sensitive to the size of the confined water core. This resonance results from size-dependent modifications in the vibrational density of states, and thus has far-reaching implications for chemical processes which involve water sequestered within small cavities. These data represent the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…Terahertz spectroscopy in reverse micelles has revealed the low vibrational modes characteristic for confined water. 21 These modes are size-dependent and support the idea of a behavior specific to water in nanoconfinement. NMR has also proven to be a valuable tool for measuring the effect of confinement on the rotational dynamics by means of a molecular probe.…”
Section: Introductionsupporting
confidence: 56%
“…Terahertz spectroscopy in reverse micelles has revealed the low vibrational modes characteristic for confined water. 21 These modes are size-dependent and support the idea of a behavior specific to water in nanoconfinement. NMR has also proven to be a valuable tool for measuring the effect of confinement on the rotational dynamics by means of a molecular probe.…”
Section: Introductionsupporting
confidence: 56%
“…The dielectric properties in the terahertz spectral range (3-33 cm -1 ) have also been reported. 35 A resonance was observed that is not present in bulk water samples and is dependent on the size of the reverse micelle. The authors attributed it to surface modes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] This is an exciting development, as it is becoming increasingly clear that many systems of interest, including biological molecules and a variety of artificial nanostructures, have absorption features in the THz frequency range, but are far smaller than the wavelength of the THz radiation. [8][9][10][11] These developments therefore offer great promise for THz microscopy. In the THz ANSOM experiments, two different detection techniques are currently employed: THz electric fields are either detected in the nearfield of the tip using electro-optic sampling, or in the far-field of the tip with a receiver.…”
mentioning
confidence: 99%